KORELASI ANTARA KONDISI LINGKUNGAN FISIK SOSIAL BUDAYA DAN SOSIAL EKONOMI DENGAN PARTISIPASI WARGA MASYARAKAT DALAM PNPM MANDIRI PERDESAN - Bona, Hamzah (JURNAL NASIONAL PARIWISATA, 2013)
The purposes of this study is to identify the correlation of physical environment, socio-cultural and socio-ecomic to the community participation by the National Program of Community Empowerment for rural areas empowering (Rural-PNPM) The research was conducted by survey method and using independent variables such as physical environment, socio-culture and socio-economic factor while the dependent variable is the community participation. Respondents are the people who particpipate directly and or indirectly to the implementation of the Rural-PNPM. They are consisting of 100 respondents by using systematic sampling technique. The data were then processced and analyzed by using simple linear regresion, multi linear regresion. This analysis aimed to find out the correlation of each independent variable to the dependent variable, and to predict changing its variables.Â The results showed that level of community participation is in mid category 61% and the inferensial statistics suggests that: First, the correlation between indenpendent and dependent variabel are quite strong category and positive with correlation cofficien value (R) 0,519. Second, determination coefficient value (R square) reaches (0,353). It indicates that the physical environment; socio-cultural and socio-ecomic factor contribute 35.3 persent to the level of community participation at the tourism development. Third, level of community participation influenced by physical environment, socio-culture and socio-economic factor. They are sanitation, age, education, activity in social organization with regression coefficient (Y = 0,509 + 0,201X1 + 0,152X2 + 0,451X3 + 0,224X4 + 0,006X5). Fourth, in partially, sanitation, education level, activity in social organization and family income variables have weak positive effect and significant to the level of community partisipation, while age a very weak positive but not significant.Â